Programming Arduino : getting started with sketches - Monk, Simon (New York : McGraw, 2012)
'Using clear, easy-to-follow examples, Programming Arduino: Getting Started with Sketches reveals the software side of Arduino and explains how to write well-crafted sketches using the modified C language of Arduino. No prior programming experience is required! The downloadable sample programs featured in the book can be used as-is or modified to suit your purposes. - Understand Arduino hardware fundamentals - Install the software, power it up, and upload your first sketch - Learn C language basics - Write functions in Arduino sketches - Structure data using arrays and strings - Use Arduino's digital and analog inputs and outputs in your programs - Work with the Standard Arduino Library - Write sketches that can store data - Program LCD displays - Use an Ethernet shield to enable Arduino to function as a web server - Write your own Arduino libraries'--
Machine generated contents note: Introduction -- Ch. 1. This Is Arduino -- Ch 2. Getting Started -- Ch 3. C Language Basics -- Ch 4. Functions -- Ch 5. Arrays, Strings and Pointers -- Ch 6. Input / Output -- Ch 7. Standard Library Goodies -- Ch 8. External Storage -- Ch 9. LCD Displays -- Ch 10. Programming for the Web -- Ch 11. Program Design -- Ch 12. C++ and Library Writing.
Keywords: Arduino (Microcontroller); Programmable controllers; TECHNOLOGY & ENGINEERING / Electronics / Microelectronics